Attitudes and Challenges of Pre-University Students in Kota Samarahan towards AI-Assisted Pronunciation Learning - Nawas, Abg. Ashmirul Abg. Abu; Yaacob, Nur Syafiqah; Hashim, Haida Umiera; Yeszhanova, Saule; Ramanair, Joseph (Journal of Cultural Analysis and Social Change, 2025)
With the rapid integration of artificial intelligence (AI) in language education, understanding students’ perceptions of AI-assisted pronunciation tools has become increasingly important. This study examines pre-university students' attitudes and challenges regarding AI-assisted English pronunciation learning in Kota Samarahan, Sarawak, Malaysia. Through a quantitative research design, a survey was employed with 120 pre-university students participated. The research found predominantly positive attitudes of which participants viewed AI tools as engaging, effective for improving pronunciation accuracy, and motivating for regular practice. They found the feedback clear and were willing to recommend these tools. Apart from that, several key challenges were identified. The most obvious issue was AI's lack of personalised guidance compared to teachers. Other significant obstacles included unreliable internet connectivity, AI systems' inaccuracies in recognising diverse accents, and the demotivating effect of repetitive feedback during extended use. The findings suggest AI tools are valuable for supplementary pronunciation practice. However, effective integration requires improved technological infrastructure, more accent-inclusive AI design, and a blended approach that combines automated feedback with teacher support to address pedagogical and motivational gaps.